1 - Preface - Diouf, Mamadou (Africa Development, 1990)
This special issue of Africa Development is devoted to democracy and democratization processes in Africa. It addresses two central themes: popular resistance to political authoritarianism (could these be identified as signs of a civil society?); and, the way in which social science techniques, methods and procedures bring out the nature of social movements and show whether or not these movements, in the process of their development, reflect the dynamic nature of the contradictions in African societies. The articles in this issue address two levels of enquiry: the crises of African societies and the crises of research methods of African scholars and Africanist sciences. Although these issues dominated the 1980s, the articles are still relevant because the same problems continue to haunt us today. The articles are worthy of discussion and debate because they mark a turningpoint in our intellectual endeavours. Based on papers presented and discussed at the Sixth General Assembly of CODESRIA in 1988, the articles highlight both the context and the ideological epistemological biases of thg time. The issue of democratization processes will be "revisited" at the next General Assembly which is to be held in December 1991. This time the exercise will be undertaken in the context of international and continental upheaval, for example, the collapse of the Eastern European political systems, the crisis of Marxism and the emergence of social movements in most African countries some of which have resulted in abrupt and sometimes violent transitions from single to multiple party systems. These papers have been published to ensure continuity in the debate with a view to following closely both the trajectory of African sooieties and the crisis of epistemological approaches which attempt to explain the present changes in African reality.